Head-to-head comparison of azvudine and nirmatrelvir/ritonavir for the hospitalized patients with COVID-19: a real-world retrospective cohort study with propensity score matching - Wei, An-Hua; Zeng, Lu; Wang, Lu; Gui, Lin; Zhang, Wen-Ting; Gong, Xue-Peng; Li, Juan; Liu, Dong (Frontiers in Pharmacology, 2023)
Background Nirmatrelvir/ritonavir and azvudine have been approved for the early treatment of COVID-19 in China, however, limited real-world data exists regarding their effectiveness and safety.We conducted a retrospective cohort study involving the hospitalized COVID-19 patients in China between December 2022 and January 2023. Demographic, clinical, and safety variables were recorded.Among the 6,616 hospitalized COVID-19 patients, we included a total of 725 patients including azvudine recipients (N = 461) and nirmatrelvir/ritonavir (N = 264) recipients after exclusions and propensity score matching (1:2). There was no significant difference in the composite disease progression events between azvudine (98, 21.26 %) and nirmatrelvir/ritonavir (72, 27.27 %) groups (P=0.066). Azvudine was associated with a significant reduction in secondary outcomes, including the percentage of intensive care unit admission (P=0.038) and the need for invasive mechanical ventilation ( P=0.035), while the in-hospital death event did not significantly differ (P=0.991). As for safety outcomes, 33 out of 461 patients (7.16%) in azvudine group and 22 out of 264 patients (8.33%) in nirmatrelvir/ritonavir group experienced drug-related adverse events between the day of admission (P=0.565).In our real-world setting, azvudine treatment demonstrated similar safety compared to nirmatrelvir/ritonavir in hospitalized COVID-19 patients. Additionally, it showed slightly better clinical benefits in this population. However, further confirmation through additional clinical trials is necessary.